2018
DOI: 10.1128/jcm.00170-18
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Toxigenic and Nontoxigenic Clostridium difficile Strains in Malaysia

Abstract: Accumulating evidence shows a high prevalence of in Southeast Asia associated with a range of clinical presentations. However, severe infections are rarely reported. We investigated infection (CDI) across four hospitals in Kuala Lumpur and Kota Bharu, Malaysia. Enzyme immunoassays for glutamate dehydrogenase (GDH) and toxin A or B were performed on diarrheal stool specimens collected from patients in 2015 and 2016. Specimens were also cultured and isolates of characterized by PCR ribotyping and detection of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 27 publications
5
24
1
Order By: Relevance
“…Less is known of the molecular epidemiology of C. difficile in South America, but RTs 027, 106, 012, 046, and 014/020 are reportedly the most common strains [31,33,34]. Similar to the current study, RT 017 (followed by RT 001) has also been found at high prevalence in South Africa [35], and in Ghana, Malawi, and Tanzania the few studies which performed molecular typing have shown a high prevalence of non-toxigenic strains [36,37], similar to reports from Southeast Asian countries [15].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Less is known of the molecular epidemiology of C. difficile in South America, but RTs 027, 106, 012, 046, and 014/020 are reportedly the most common strains [31,33,34]. Similar to the current study, RT 017 (followed by RT 001) has also been found at high prevalence in South Africa [35], and in Ghana, Malawi, and Tanzania the few studies which performed molecular typing have shown a high prevalence of non-toxigenic strains [36,37], similar to reports from Southeast Asian countries [15].…”
Section: Discussionsupporting
confidence: 89%
“…Due to uncertainty about whether they were carried with a toxigenic strain, cases, where they were isolated, were excluded from the logistic regression analyses. The prevalence of colonization with non-toxigenic strains in Asian countries appears to be high among hospital inpatients (10.4-28.6%) [15][16][17]27,41]. This is interesting given that clinical trials have found that administration of non-toxigenic strains reduces risk of recurrent infection in CDI cases [42], making it plausible that the high prevalence of colonization with non-toxigenic strains in Asia-Pacific countries may explain the low rate of recurrent CDI found in this study.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Surprisingly, several RTs identified in our study carried toxin genes (RTs 031, 038, 039, 084, 085) but in other studies an absence of the toxin genes in these ribotypes was identified [28,[45][46][47][48][49][50][51]. The differences in PaLoc arrangements in certain RTs were also noted previously.…”
Section: Discussionsupporting
confidence: 75%
“…This rate had a mild influence on the specificity of both GDH tests in this study, which was kept above 92%. Although the rates of patients with nontoxigenic strains are generally similar to that seen in this study [5,19], there are reports of rates higher than 50% in some other institutions [18,[20][21][22]. Thus, it should be considered that the use of GDH as a single method should be preceded by an evaluation of its specificity and PPV in the institution, thus avoiding unnecessary antimicrobial treatment for CDI in asymptomatic carriers [9].…”
supporting
confidence: 73%